International Tailored Chemotherapy Adjuvant (ITACA) trial, a phase III multicenter randomized trial comparing adjuvant pharmacogenomic-driven chemotherapy versus standard adjuvant chemotherapy in completely resected stage II-IIIA non-small-cell lung cancer - Novello, Silvia; Torri, V.; Grohé, Christian; Kurz, S.; Serke, M.; Wehler, T.; Meyer, A.; Ladage, D.; Geissler, M.; Colantonio, I.; Cauchi, C.; Stoelben, E.; et al. (Annals of oncology, 2022)
Background - Several strategies have been investigated to improve the 4% survival advantage of adjuvant chemotherapy in early-stage non-small-cell lung cancer (NSCLC). In this investigator-initiated study we aimed to evaluate the predictive utility of the messenger RNA (mRNA) expression levels of excision repair cross complementation group 1 (ERCC1) and thymidylate synthase (TS) as assessed in resected tumor. - Patients and methods - Seven hundred and seventy-three completely resected stage II-III NSCLC patients were enrolled and randomly assigned in each of the four genomic subgroups to investigator’s choice of platinum-based chemotherapy (C, n = 389) or tailored chemotherapy (T, n = 384). All anticancer drugs were administered according to standard doses and schedules. Stratification factors included stage and smoking status. The primary endpoint of the study was overall survival (OS). - Results - Six hundred and ninety patients were included in the primary analysis. At a median follow-up of 45.9 months, 85 (24.6%) and 70 (20.3%) patients died in arms C and T, respectively. Five-year survival for patients in arms C and T was of 65.4% (95% CI (confidence interval): 58.5% to 71.4%) and 72.9% (95% CI: 66.5% to 78.3%), respectively. The estimated hazard ratio (HR) was 0.77 (95% CI: 0.56-1.06, P value: 0.109) for arm T versus arm C. HR for recurrence-free survival was 0.89 (95% CI: 0.69-1.14, P value: 0.341) for arm T versus arm C. Grade 3-5 toxicities were more frequently reported in arm C than in arm T. - Conclusion - In completely resected stage II-III NSCLC tailoring adjuvant chemotherapy conferred a non-statistically significant trend for OS favoring the T arm. In terms of safety, the T arm was associated with better efficacy/toxicity ratio related to the different therapeutic choices in the experimental arm.
Online verfügbar: 5. Oktober 2021, Artikelversion: 16. Dezember 2021
Gesehen am 20.08.2024